Eccentric Torque-Producing Capacity is Influenced by Muscle Length in Older Healthy Adults. Issue 1 (January 2016) - Melo, Ruth C.; Takahashi, Anielle C.M.; Quitério, Robison J.; Salvini, Tânia F.; Catai, Aparecida M.
Abstract : Abstract: Melo, RC, Takahashi, ACM, Quitério, RJ, Salvini, TF, and Catai, AM. Eccentric torque-producing capacity is influenced by muscle length in older healthy adults. J Strength Cond Res 30(1): 259–266, 2016—Considering the importance of muscle strength to functional capacity in the elderly, the study investigated the effects of age on isokinetic performance and torque production as a function of muscle length. Eleven younger (24.2 ± 2.9 years) and 16 older men (62.7 ± 2.5 years) were subjected to concentric and eccentric isokinetic knee extension/flexion at 60 and 120°·s −1 through a functional range of motion. The older group presented lower peak torque (in newton-meters) than the young group for both isokinetic contraction types (age effect, p < 0.001). Peak torque deficits in the older group were near 30 and 29% for concentric and eccentric contraction, respectively. Concentric peak torque was lower at 120°·s −1 than at 60°·s −1 for both groups (angular velocity effect, p < 0.001). Eccentric knee extension torque was the only exercise tested that showed an interaction effect between age and muscle length ( p < 0.001), which suggested different torque responses to the muscle length between groups. Compared with the young group, the eccentric knee extension torque was 22–56% lower in the older group, with the deficits being lower in the shortened muscle length (22–27%) and higher (33–56%) in the stretched muscle length. In older men, the production of eccentric knee strength seems to be dependent on the muscle length. At more stretched positions, older subjects lose the capacity to generate eccentric knee extension torque. More studies are needed to assess the mechanisms involved in eccentric strength preservation with aging and its relationship with muscle length.